OSTALGIA AND NON-REVERSIBILITY IN THE CENTRAL EUROPEAN CINEMA OF THE TURNING POINT - Dabert, Dobrochna (Porównania, 2012)
The text is dedicated to ostalgia – a deformed memory of communism which appeared in the countries of the former Eastern bloc where it is reflected in the public discourse, historical and politological debates, in forms of media activity but also in literary and cinema arts. Ostalgia assumes various forms which base on local conditions: the shape and intensity of the post-war regime, historical, social, moral and mental contexts. The features which allow to present the specificity of the ostalgic memory are: selectivity, inaccuracy and imperfection. If ostalgia is built on the sentiment towards some aspects of the past then its negation, which can be called non-reversibility,originates from resentiments towards the past and are visible in the unwillingness towards recollection, a flight from the past into presentism but also reaching the darkest experience of the communist times. The text reveals the phenomenon of ostalgia and non-reversibility found in Central European films produced after the breakthrough of 1989.